Knowledge utilization and decision making in construction projects in Malaysia - Alashwal, Ali Mohammed; Ng, Wen Si (2016)
Knowledge utilization is the process to apply right and relevant knowledge at the right time and place for effective decision making.The purpose of this paper is twofold.First, to identify the characteristics of knowledge utilization in construction projects in Malaysia.Second, to test whether there is an influence of knowledge utilization on decision making.A questionnaire survey was used to collect data from 124 professionals in different types of construction projects.Processes, factors, and obstacles of knowledge utilization were identified and discussed in this paper.However, the results indicated that there is no significant relationship between knowledge utilization and effectiveness of decision making.